The metamorphosis: from the people to the multitude - Bailon Maxi, Jaime Enrique (2024)
The notion of the people and popular sovereignty are essential elements of the idea of a republic. Throughout history, the concept of the people has undergone various transformations, yet it has always maintained a tendency towards identity and homogeneity and has been, by excellence, the agent of power, even in monarchies, because paradoxically the king was the embodiment of the people. On the other hand, the multitude, this social subject shaped by processes of capitalist globalization and the diaspora of millions of human beings, is rather a multiplicity, a plane of diverse singularities that communicate with each other and will develop new tactics of struggle and new forms of cultural production. In this article, we will develop a critical reflection on the images of the notion of the people that shaped the political and cultural elites during the main historical events of independent Peru. Finally, we will conclude by analyzing how the figure of the people has been evolving in the late 21st century into the body of the multitude.